Textbook of medical biochemistry - Chatterjea, MN; Shinde, Rana (New Delhi : Japee Brothers, 2008)
The text has been fully revised and updated keeping in view the suggestions received from alert readers and the disccussions held with the students and academicians.
Section One: Cell Biology Section Two: Chemistry of Biomolecules Section Three:Molecula Biology Section four: Metabolism Section five : Clinical Biochemistry and other ...
Incluye índice, glosario Texto en inglés
Keywords: BIOCHEMISTRY; METABOLISM; MOLECULAR BIOLOGY